Cardiovascular risk and its influencing factors during exercise in apparently healthy Chinese adult population - Zhipeng Zeng; Hang Zhao; Juan Wang; Peng Pi; Li Hao; Yan Wang; Zhengzhen Wang (BMC, 2024)
Abstract Background There are few studies on the safety of sub-maximal exercise testing of aerobic exercise in apparently healthy Chinese populations. The purpose of this study was to explore the frequency of exercise electrocardiography (ECG) abnormalities and the corresponding exercise intensities, as well as the associated influencing factors, during a symptom-limited stepwise incremental cardiopulmonary exercise test (CPET) in an apparently healthy Chinese population. Methods A cross-sectional study was done in four communities, one urban and one rural in the North (Beijing) and in the South (Hezhou, Guangxi) of China from 1 January 2017 to 31 December 2018, respectively. Total of 1642 participants was recruited, 918 were eligible and completed demographic indicators, routine blood indicators, physical activity status, symptom-limited CPET and exercise ECG were included in the analysis. Results Of the exercise ECG outcomes, 10 (1.1%) were positive and occurred at exercise intensities ≥ 62.50% heart rate reserve (HRR); 44 (4.8%) were equivocal and 864 (94.1%) were normal. Individuals with Cardiovascular Disease Risk Factor (CVDRF) = 3-4 were 2.6 times more likely to have a equivocal and abnormal exercise ECG than those with CVDRF = 0-2. Exercise ECGs of individuals with CVDRF = 5-7 were 5.4 times more likely to be positive and abnormal than exercise ECGs of individuals with CVDRF = 0-2. Conclusions The exercise intensity of 62.5% HRR can be used as a safe upper limit for safe participation in exercise in apparently healthy Chinese population; the greater the number of CVDRFs, the greater the likelihood of cardiovascular risk during exercise.